Influence of strength, endurance and concurrent training on the lipid profile and blood testosterone and cortisol response in young male wrestlers - Mirghani, S. J.; Alinejad, H. A.; Azarbayjani, M. A.; Mazidi, A.; Mirghani, S. A. (Baltic Journal of Health and Physical Activity, 2014)
Background: There is little information regarding the effects of concurrent training (endurance and resistance training) on the fat profile, blood testosterone and cortisol response. The aim of the study was to investigate the effect of eight weeks of concurrent training on the fat profile, blood testosterone and cortisol response in young male wrestlers.